Blown film extrusion - Cantor, Kirk (Hanser Publications, 2011)
From hardware and materials through processing and properties, a broad coverage of blown film extrusion is presented. A primary objective of this book is to ensure a useful balance of theory and practice. The reader will find the answers to "Why?" they encounter certain effects in the blown film process so that they are better able to troubleshoot and improve their operations. At the same time, current practices and equipment are emphasized to keep readers up-to-date with the most productive and efficient technology. The companion CD-ROM, The Blown Film Extrusion Simulator, is provided to enhance the learning process. This software was developed specifically to teach blown film extrusion equipment operation and processing principles. The realistic graphic interface and intuitive operating techniques were designed to emulate actual processing methods so that learners can quickly move from the simulator to real production equipment. Throughout this book, exercises using the simulator are described to complement the methods and principles explained. Readers are encouraged to take a break from the book and spend a few minutes with the simulator to enhance their understanding of the content